Investigating the Presence of eap and spa Genes of Staphylococcus aureus and their Relation to Antibiotic Resistance - Shakur , Jilan Ahmed; Aburesha , Rasmiya Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Staphylococcus aureus is an extracellular and intracellular microbe that can infect different mammalian cells like epithelial, endothelial, and osteoblasts. It is a source of recurrent infection and has persistently caused a variety of human diseases, like skin infections and systemic diseases such as osteomyelitis, endocarditis, pneumonia, bacteremia, sepsis, and toxic shock syndrome. Diagnosed (30) isolates of S. aureus have been taken from urine. A clinical sample has been done according to the culture on mannitol salt agar and biochemical tests, then identification through amplification of the 16srRNA gene by conventional PCR, detection of spa and eap genes by conventional PCR found all isolated to have a spa gene with a percentage of 100% but an eap gene found with a percentage of 53.3%, and detection of their relation with antibiotic resistance found 76.70% of this isolates resistance to different types of antibiotic. Many factors contributed to the rapid development of antimicrobial resistance, including cell membrane disruption, environmental factors, and DNA damage. All of these factors contributed to the rapid development of antibiotic resistance. Staphylococcus aureus is resistant to a lot of commonly used antibiotics, such as Beta-lactams, Tetracycline, Aminoglycosides, Fluoroquinolones, Macrolides, and Chloramphenicol.